Effects of acetic acid on efficiency of collagen extraction from jellyfish \(Rhopilema hispdium\) (Vanhöffen, 1888) - Pham Thi , Kha; Pham The, Thu; Tran Manh , Ha; Chu Van , Thuoc; Le Ba , Hoang Hiep (Vietnam Journal of Marine Science and Technology, 2021)
Collagen is an extremely important fibrous protein in the body. It is the main structural material of all tissues: Skin, bones, ligaments, tendons, cartilage. The source of traditional collagen production is mainly from the skin and bones of animals. However, marine animals are currently a promising alternative source of materials with low risk of disease transmission, no religious barriers to consumption, abundant raw materials, and high-efficiency extraction. In present study, the effects of several factors: Acetic acid concentration, the ratio of jellyfish and acetic acid solution (w:v), as well as the time of extraction on efficiency of collagen extraction process from jellyfish (Rhopilema hispidum Vanhoffen, 1888) were investigated. The results showed that the collagen which was extracted from jellyfish in 0.1M acetic acid, with the ratio 1:3 between the jellyfish and acetic acid solution (w:v) in 5-day extraction had high extraction efficiency. Extracted collagen in present study was mainly type I collagen, consisting of 3 polypeptide chains: β chain ( 250 kDa), α1 chain ( 40 kDa) and α2 chain ( 100 kDa).